Literature Review: Major Depression with Somatic Comorbidities - Andini Yusuf; Muhammad Alim Jaya; Zulfitriani Murfat (Newinera Publisher, 2026)
Major depressive disorder (MDD) is a mood disorder often accompanied by somatic symptoms and chronic physical illness. Complaints such as pain, fatigue, insomnia, headaches, and palpitations are often the primary reasons patients seek medical help, often resulting in a delayed diagnosis. This study aims to determine the relationship between major depression and somatic comorbidities based on published research. The method used was a literature review with a narrative review design. Articles were searched in the PubMed and Google Scholar databases using the keywords